Hirudotherapy - Younis, Khansaa Aziz (American Journal of Biology and Natural Sciences, 2025)
Hirudo medicins have been used in human medicine to treat many diseases hundreds of years ago, such as vascular diseases, muscle and joint diseases, migraines, eye diseases, impotence , hemorrhoids and depression. Treating varicose veins is also among the common therapeutic applications of leeches. Leech treatment is also considered a type of complementary or alternative medicine, as there are 650 types of leeches around the world. Perhaps one of the most important diseases of the blood vessels is venous congestion after surgical operations. In the world of reconstructive surgery, which has witnessed a renaissance in recent years, medical leeches have been used. In particular, it reduces venous congestion and restores venous drainage after performing amputated finger transplants, in addition to the subsequent anticoagulant effect of leech enzymes within 5-6 hours after performing such operations. Previous studies indicated that treatment with medical leeches has benefits for persons with venous congestion in the tissues and skin, reimplantations skin flaps , inflammation of the salivary glands, swelling, excessive lingual swelling , and osteoporosis, in addition to various types of ulcers. also It has been proven that this treatment has anti-inflammatory and pain reliever, anticoagulant effects , It is a blood and lymphatic enhancer, . Hirudin is one of the most important substance in leech saliva , which prevents blood clotting and acts as an anti-coagulant agent.